Prevalence and determinants of sexting behaviour among undergraduates in Kawara State - Balogun Abdulrasaq Olatunji; Obimuyiwa Gabriel Ayodeji; Abdulaziz Isiaka; Oniye Oniye (Journal of Education and Learning (EduLearn), 2019)
This study investigates the prevalence and determinants of sexting behaviour among undergraduates in Kwara State. The population for this study comprised all undergraduates in Kwara State while the target population was undergraduates of three universities in the Kwara States. A stratified sampling the technique was used to categorise universities based on ownership (Federal, State and Private) as well as gender. A random sampling technique was used to select 100 undergraduates from each university, totaling 300 respondents. A researcher-designed questionnaire titled Prevalence and Determinants of Sexting Behaviour Questionnaire (PASODOEBEQ) was used to elicit information from sampled respondents. The instrument was validated by experts in Sociology of Education and Educational Psychology. Test re-test method of reliability was applied to test the reliability of the instrument, using the Pearson Product Moment Correlation statistics. The coefficient value of 0.86r was derived. The data collected were analyzed using percentage, mean, standard deviation and Multiple Regression Statistical Tool. The result of the findings revealed that sexting behaviour is prevalent among undergraduates and low self-esteem and peer association are significant determinants. The study recommended among others that schools authorities as a matter of fact should organize a sensitization workshop or seminar for undergraduates on the meaning, ripple effects and the punishment associated with sexting behaviour for necessary social adjustment.